Differential pathways into smoking among sexual orientation and social class groups in England: A structural equation model. (1st August 2019) - Davies, Megan; Lewis, Nathaniel M.; Moon, Graham
Highlights: English LGB groups may be overlooked in strategies to reduce smoking inequalities. Lower mental wellbeing is a key pathway into smoking for English LGB individuals. LGB smoking risks may be distinct from those affecting lower social class groups. National context may explain lack of age- or exposure-based pathways for LGB groups. English LGB groups require more targeted smoking prevention and cessation efforts. Abstract: Purpose: Previous research has shown that lesbian, gay and bisexual (LGB) populations smoke more than their heterosexual counterparts. Little is known about the pathways into smoking among LGB populations in England relative to the lower social class populations that are the focus of the current Tobacco Control Plan (TCP). Methods: Using the 2013/2014 waves of the Health Survey for England (HSE), we created a structural equation model to analyze pathways and interactions between sexual orientation, social class, and the number of cigarettes smoked daily. The path analysis assessed whether three intervening factors—age of initiation, mental wellbeing score, and exposure to smoke—are implicated similarly in smoking among LGB and lower social class populations, and whether interaction between sexual orientation and class is further associated with smoking. Results: Bivariate analysis showed that LGB-identified individuals and individuals in lower occupational classes smoke more cigarettes daily, respectively, than heterosexual individuals and those in professional/managerial-class populations. Path analysis showed that the number of cigarettes smoked daily was mediated by age of initiation, mental wellbeing score and weekly exposure to smoke among routine and manual workers; by mental wellbeing score and exposure to smoke among intermediate class workers, and by mental wellbeing score in the LGB population. Interactions between sexual orientation and social class were not significant. Conclusions: The differential nature of pathways into smoking for lower social classes and LGB populations in England suggests the need for tailored prevention and cessation efforts, with programming for LGB populations focused on the distinct stressors they face.